Changes in growth and pigment content in Sweet potato by triadimefon and hexaconazole - R. Panneerselvam, T. Sivakumar, A. Sundaramanickam, (Journal of Phytology, 2009)
Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Triadimefon and hexaconazole are triazole group of fungicides have plant growth regulating properties. The present investigation aimed to study the growth regulating effect of these compounds on sweet potato (Ipomoea batatas L.). Each plant was treated with one litre of aqueous solutions containing 15mg L-1 triadimefon and 10mg L-1 hexaconazole on 40 and 70 days after planting (DAP) by soil drenching. The growth parameters of the plants were estimated on 45, 60, 75, 90 and 105 DAP.Ã‚Â Among the triazole, hexaconazole inhibited the number of leaves, total leaf area, stem length, internodal length, leaf and stem dry weight, relative shoot growth rate significantly when compared to triadimefon.Ã‚Â Triazole (chiefly available and plant control and yield production) treatments increase the root length, root and tuber dry weight, relative tuber growth rate, net assimilation rate root/shoot ratio, leaf dry weight per unit area, chlorophyll and carotenoid content.